2013
DOI: 10.7314/apjcp.2013.14.9.5477
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Communication Difficulties in Pediatric Hematology: Oncology Nurses

Abstract: Caring for patients with chronic or life-threating illnesses, communication and relationships with patients and other healthcare professionals are common themes that cause concerns in oncology nurses (Dowling, 2008;Van Rooyen et al., 2008). Palsson and Norberg (1995) 5478 managing stres, the quality and safety of patient care, cost effectiveness, and the retention of nurses (Wilkinson et al., 2008; Steward et al., 2010 Materials and Methods Sample and study designThis descriptive qualitative study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…Knowledge of effective communication skills is much more important in cases where the anxiety of children and their families is increased, such as in cases of cancer in children (Xie et al, 2013). Citak et al (2013) also reported that nurses working in paediatric oncology clinics experienced communication problems, had difficulty in maintaining professional communication and requested that training programs on this subject matter be arranged. The same study reported Experiences of Nursing Students with Pediatric Cancer Patients that nurses experienced inadequacy, exhaustion and avoidance of communication with children with cancer and their families as the result of communication problems they had experienced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of effective communication skills is much more important in cases where the anxiety of children and their families is increased, such as in cases of cancer in children (Xie et al, 2013). Citak et al (2013) also reported that nurses working in paediatric oncology clinics experienced communication problems, had difficulty in maintaining professional communication and requested that training programs on this subject matter be arranged. The same study reported Experiences of Nursing Students with Pediatric Cancer Patients that nurses experienced inadequacy, exhaustion and avoidance of communication with children with cancer and their families as the result of communication problems they had experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that even nurses trained in the care of cancer patients experience many challenges during the caregiving (Meraviglia et al, 2003;Citak et al, 2013). For this reason, health professionals caring for cancer patients must have knowledge about the nature, diagnosis and treatment of cancer, how to communicate effectively with paediatric cancer patients and their families and how to care for paediatric cancer patients and their families in the terminal period (Meraviglia et al, 2003).…”
Section: Experiences Of Nursing Students In Caring For Pediatric Cancmentioning
confidence: 99%
“…Prior research generally confirms that families and family members in paediatric oncology nursing can be a source of reward as well as stress for nurses. Citak, Toruner and Gunes (2013) learned that paediatric oncology nurses experience communication difficulties with children and their families during long hospital stays. They posit that communication difficulties increase during crisis periods, such as the time of first diagnosis, relapse and the terminal stage, or on days with special meaning, such as holidays.…”
Section: Paediatric Oncology Nursingmentioning
confidence: 99%
“…They posit that communication difficulties increase during crisis periods, such as the time of first diagnosis, relapse and the terminal stage, or on days with special meaning, such as holidays. Nurses experience that communication difficulties lead to feelings of incompetence, exhaustion or difficulties in coping (Citak et al, 2013). Feelings of reward have also been reported: Enzman and Gaughan (2014) indicated that when a paediatric nurse coaches parents and family as a caregiver, the caring is reflected in the relationship, which can be particularly rewarding to nurses.…”
Section: Paediatric Oncology Nursingmentioning
confidence: 99%
“…A significant portion of health care costs is devoted to labs (McClatchy, 2002;Kalra, 2004 (Bonini et al, 2002;Citak et al, 2013). According to the Pentagon reports, people who die from medical errors each year in the United States are more than the number of Americans killed in the Korean and Vietnam Wars.…”
Section: Introductionmentioning
confidence: 99%